Emodin alleviates intestinal ischemia-reperfusion injury through antioxidant stress, anti-inflammatory responses and anti-apoptosis effects via Akt-mediated HO-1 upregulation - Yinyin Liu; Tuo Ji; Haixing Jiang; Meng Chen; Wanli Liu; Zongze Zhang; Xianghu He (BMC, 2024)
Abstract Background Intestinal ischemia-reperfusion (I/R) injury is a severe vascular emergency. Previous research indicated the protective effects of Emodin on I/R injury. Our study aims to explore the effect of Emodin on intestinal I/R (II/R) injury and elucidate the underlying mechanisms. Methods C57BL/6 mice and Caco-2 cells were used for in vivo and in vitro studies. We established an animal model of II/R injury by temporarily occluding superior mesenteric artery. We constructed an oxygen-glucose deprivation/reoxygenation (OGD/R) cell model using a hypoxia-reoxygenation incubator. Different doses of Emodin were explored to determine the optimal therapeutic dose. Additionally, inhibitors targeting the protein kinase B (Akt) or Heme oxygenase-1 (HO-1) were administered to investigate their potential protective mechanisms. Results Our results demonstrated that in animal experiments, Emodin mitigated barrier disruption, minimized inflammation, reduced oxidative stress, and inhibited apoptosis. When Akt or HO-1 was inhibited, the protective effect of Emodin was eliminated. Inhibiting Akt also reduced the level of HO-1. In cell experiments, Emodin reduced inflammation and apoptosis in the OGD/R cell model. Additionally, when Akt or HO-1 was inhibited, the protective effect of Emodin was weakened. Conclusions Our findings suggest that Emodin may protect the intestine against II/R injury through the Akt/HO-1 signaling pathway.